The Effect Of Capital Intensity, Sales Growth, Leverage On Tax Avoidance And Profitability As Moderators - Farid Addy Sumantri; Agus Kusnawan; Rr. Dian Anggraeni (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to examine the effect of capital intensity, sales growth, leverage on tax avoidance and profitability as a moderator. Tax Avoidance in this study was measured using the cash effective tax rate (CETR) approach and leverage was measured using the debt to equity ratio (DER). Profitability as a moderating variable is measured using return on assets (ROA). The research sample uses food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The research method used is a purposive sampling approach. The number of companies used in this study were 11 companies with a research period span of five years, so the number of samples used in this study was 55 samples. The model in this study uses multiple linear regression. The results of the study prove that the variables of capital intensity and sales growth have an effect on tax avoidance. On the other hand, leverage proxies with DER has no effect on tax avoidance. The results of this study can also prove that profitability is proxyed by return on assets to moderate the effect of leverage on tax avoidance. On the other hand, profitability as proxied by return on assets cannot moderate the effect of capital intensity and sales growth on tax avoidance.